Approaching Resilience for Climate Change Adaptation in Complex Milieus: The Case of Vulnerable Neighborhoods in Cartagena de Indias - Luna-Galván, Mauricio; Vargas-Chaves, Iván (European Journal of Sustainable Development, 2018)
Tackling related climate change impacts and extreme weather events in urban areas located in developing countries is increasingly becoming a challenge for several stakeholders. Responses to such impacts are being framed and addressed by strategies and policies under the climate change adaptation and mitigation frameworks. However, approaching resilience and adaptive capacities are ever more in need in complex neighborhoods, especially when these are facing climate impacts such as flooding. Framing social dimensions into that adaptive capacity in complex urban systems characterized by poverty, exclusion and the poor public services access makes harder their living standards. Thereby, frameworks taking into account social elements and key indicators of inclusiveness, contribute to the understanding of the social fabrics based on the living conditions of disadvantaged localities. This special issue explores resilience in the wake of climate-related events such as flooding in neighborhoods with striking social, economic and environmental conditions. Studying the case of the flood-suffering neighborhood of Fredonia in Cartagena, Colombia, will shed light on this particular issue by providing relevant evidence that the levels of climate impacts and hazards occurring in vulnerable urban areas in developing countries, rely on particular social traits that ultimately undermine adaptation efforts for resilience, hence becoming a social problem. Keywords: Climate Change Adaptation; Climate Events; Resilience; Urban Complexities; Urban Inclusiveness; Vulnerable Neighborhoods.